Transcatheter aortic valve implantation: long-term clinical outcome and valve durability - Sulzenko, Jakub; Tousek, Petr; Kocka, Viktor; Widimsky, Petr (Expert review of medical devices, 2015)
Transcatheter aortic valve implantation (TAVI) is a widely used intervention in patients who are at high risk or contraindicated for cardiac surgery. The procedure is technically feasible in most patients and has very good mid-term clinical outcomes. In this special report, we evaluated the long-term outcome after TAVI and durability of percutaneously implanted aortic valve prostheses by reviewing all available long-term follow-up data. We herein present the clinical and hemodynamic data derived from patients 2-5 years after TAVI and describe all published cases of prosthesis degeneration.
Keywords: aortální chlopeň; transkatetrální implantace aortální chlopně; hemodynamika; Transcatheter Aortic Valve Replacement; lidé; časové faktory; výsledek terapie; Time Factors; Hemodynamics; Treatment Outcome; Aortic Valve; Humans